Agricultural Dualism, Wage Inequality and Development Policies - Nag, Ranjanendra Narayan; Banerjee, Rakhi (International Journal of Sustainable Agricultural Research, 2014)
The main purpose of this paper is to explore how globalization affects wage inequality and welfare in a small open economy characterized by agricultural dualism . By using a three- sector general equilibrium model we establish the possibility of a decline in welfare in the trail of different liberalization measures.In particular, we examine effects of agricultural trade liberalization and capital market liberalization. We demonstrate that implicatins of these liberalization measures for welfare and wage gap are critically sensitive to agricultural dualism, factor specificity and factor intensity ranking.